Implementation of extensive citrus triploid breeding programs based on 4x x 2x sexual hybridisations - Aleza, Pablo; Juárez, José; Hernandez, M.; Ollitrault, Patrick; Navarro, Luis (2017)
Seedlessness is one of the most important characteristics for mandarins for the fresh-fruit market, and mandarin triploid hybrids have this trait. Triploid citrus plants can be recovered by 4x x 2x hybridisations using non-apomictic genotypes as female parents. In this study, we characterise the type of seeds obtained in 4x x 2x hybridisations and the ploidy level of plants recovered from each type of seed. The majority of the plants recover were triploid (98.3 %), but a few diploid, tetraploid and pentaploid plants were also produced and their genetic origin was analysed by simple sequence repeat (SSR) markers. We also analysed the influence of parents and environmental conditions on the efficiency of recovery triploid hybrids. In this work, we present an effective methodology to recover triploid hybrids from 4x x 2x hybridisations based on in vitro embryo rescue and determination of ploidy level by flow cytometry that allow us to recover more than 4,400 triploid hybrids from more than 60 parental combinations.